Clinical research progress on pathogenesis and treatment of Patent Foramen Ovale-associated stroke - Li, Wenyao; Zhang, Jianjun; Zhang, Yier; Shentu, Wuyue; Yan, Sicheng; Chen, Qiulu; Qiao, Song; Kong, Qi (Frontiers in Neurology, 2025)
Patent Foramen Ovale (PFO), a common cardiac abnormality, has been established as the most prevalent cause of Cryptogenic Stroke (CS). In 2022, the American Society of Cardiovascular Angiography and Interventions (SCAI) officially defined PFO-induced CS as PFO-Associated Stroke (PFO-AS), whose onset characteristics and treatment methods are currently the focus of pertinent clinical research. Previously, the pathogenesis of PFO-AS was commonly believed to be related to Paradoxical Embolism (PDE) or in situ thrombosis. Recently, atrial heart disease, which could lead to abnormal cardiac structure and circulating biomarker accumulation, potentially causing vascular endothelial injury and promoting thrombosis, has also been associated with the pathogenesis of PFO-AS. Therefore, PFO-AS could be the outcome of multiple pathogenesis mechanisms. Furthermore, significant research progress has been made in elucidating the pathogenic PFO gene. Nonetheless, additional in-depth research is still required to better elucidate the precise mechanisms underlying PFO-AS. Notably, the clinical and imaging characteristics of PFO-related Ischemic Stroke (IS) are slightly different from those of other IS causes. Furthermore, the assessment of the correlation between PFO and stroke mostly relies on The Risk of Paradoxical Embolism Score (RoPE) and PFO-Associated Stroke Causal Likelihood classification (PASCAL) system, which could be a limitation. Additionally, PFO examinations mainly relied on cardiac anatomy evaluation in the past, highlighting another potential gap. Moreover, recent research suggests that PFO closure may increase the risk of Heart Failure (HF) with preserved Ejection Fraction (HFpEF). Conversely, after 2017, four Randomized Controlled Trials (RCTs): CLOSE, RESPECT, REDUCE, and DEFENSE-PFO, demonstrated that transcatheter PFO closure is more effective in preventing various risk events than conventional pharmacotherapy. This review comprehensively summarizes the latest research progress on PFO-AS pathogenesis, treatment, prevention, and management decisions, providing a valuable clinical reference.